NEW MATERIALISM - THE TRANSFORMATION OF INTELLIGENT TEXTILES TOWARDS AN INTERACTIVE YOUSER GENERATED INTERFACE - Bettina Schülke (European Scientific Journal, ESJ, 2014)
New materialism of smart or intelligent textiles represents the next generation of fibers. While textiles previously were responsible for several technological developments, today the rapid change of new technologies show their significant influence in the development of smart textile materials. As varying as their definitions are, are their applications. It is without any doubt that the most exciting developments today are taking place in the field of nanotechnology textiles. While lots of research in this area is connected with materialism research, there is a need of developing new models for creative applications and new design strategies. These novel materials generate new types of expressiveness and have the potential to transform craft and textile design into new types of artistic practice. Along with the shift from a passive functionality of static textiles towards mobility and active behavior, the users role itself is changing drastically. A multisensory and intermodal movement of thinking characterizes the intercourse with this new materialism of textiles.